Country-wide genotyping of Mycobacterium tuberculosis complex in Singapore, 2011–2017. (May 2022) - Kam, Michelle Li Wei; Lim, Leo K.Y.; Sng, Li-Hwei; Ong, Rick Twee-Hee; Lee, Vernon J.M.; Wang, Yee Tang; Chee, Cynthia B.E.
Abstract: Objective: To describe the molecular epidemiology of Mycobacterium tuberculosis complex (MTBC) and factors associated with its transmission in Singapore. Methods: Spoligotyping, 24-loci mycobacterial interspersed repetitive units – variable number of tandem repeats (MIRU-VNTR) typing and demographic data from the national TB notification registry of MTBC culture-positive cases notified from January 2011 to December 2017 were analysed. Results: Of the 12, 046 culture-positive cases notified, complete spoligotyping and MIRU-VNTR typing results were available for 8690 (72.1%) belonging to 4950 (57.0%) local-born and 3740 (43.0%) foreign-born persons. From these, 4810 (55.3%) were identified in 883 clusters. The proportion of recent transmission was 45.2%. The East-Asian Lineage 2 accounted for 4045 (47.1%) of isolates, and disproportionately accounted for large clusters. Clustered cases were more likely to be older than 50 years, male, Malay, local-born, Singapore citizens or Permanent Residents, of lower socioeconomic status, imprisoned; to harbour East-Asian Lineage 2 strain; to have cavitary pulmonary TB, positive sputum smear or be recalcitrant treatment defaulters. They were less likely to have multidrug-resistant, or isoniazid or rifampicin mono-resistant TB. Conclusion: We demonstrated the diversity of MTBC strains and, notwithstanding the likely over-estimation of clustering using these genotyping methods, elucidated factors associated with TB transmission in Singapore.